JSN 45 Mentoring for Students Through Collaboration with Indonesian Veterans as a Nationalism Strengthening Means: Pendampingan JSN 45 Untuk Mahasiswa Melalui Kolaborasi Dengan Veteran Indonesia Sebagai Sarana Penguatan Nasionalisme - Miskawi Miskawi; Harjianto Harjianto; Roudhotul Jannah; Siti Napisah; Diah Putri Wulan Dhari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
This activity aims to strengthen student nationalism through mentoring the Spirit, Spirit, and Struggle Values ​​of 1945 (JSN 45). The activity was carried out by involving Indonesian Veterans as contextual learning resources. The activity was carried out using a participatory and educational approach through coordination with the Veterans Legion of the Republic of Indonesia (LVRI), delivering national material, sharing veteran experiences, discussions, reflections, and activity evaluations. The program targets students of the History Education Study Program, Pancasila and Citizenship Education, and Guidance and Counseling at Universitas PGRI Banyuwangi. The results of the activity showed that the involvement of veterans was able to increase students' understanding of nationalism, historical awareness, and the values ​​of the nation's struggle. Students actively participated in the activity and were able to identify the application of JSN 45 values ​​in academic and social life. Collaboration between university academics and LVRI is an effective strategy in strengthening national character through contextual and experience-based learning. Similar activities need to be developed continuously to support the formation of a young generation with character and a commitment to nationalism.